EXTRACTION AND CHARACTERISTICS OF YELLOW SEA CUCUMBER (Stichopus ocellatus) COLLAGEN USING KOH SOLUTION - Yusuf Eko Syafti; Mery Sukmiwati; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
Abstract Sea cucumbers are one of the marine products that have long been an international trade commodity. This high-economy animal has various nutritional contents, including protein, fat, calcium, sodium, phosphorus and minerals as well as collagen. Research on the optimization of extraction and physicochemical characterization of collagen from yellow sea cucumber meat needs to be carried out, considering the characteristics of collagen from sources that different, one of which is to use yellow sea cucumbers as an ingredient for making collagen. The yield of collagen obtained was 5.02% (ww). The results of the functional group analysis of sea cucumber collagen using FTIR produced absorption peaks which included amide A, amide B, amide I, amide II, and amide III. The best treatment was T2 with the wave number of amide II at 1480 -1575 cm-1 indicating the presence of C-N stretching and N-H bending with strong intensity. The analysis of amino acid profiles in treatment T2 (KOH 0.3%) had 17 types of amino acids consisting of 9 types of essential amino acids and 8 types of non-essential amino acids. The highest types of essential amino acids were lysine (11.54%) and non-essential glycine with a value (12.63%). Keywords: collagen, KOH solution, sea cucumber